Developing social capital for collaboration in a research-practice partnership. Issue 4 (15th October 2018) - Klar, Hans W.; Huggins, Kristin Shawn; Buskey, Frederick C.; Desmangles, Julie K.; Phelps-Ward, Robin J.
Abstract : Purpose: The ever-increasing pressure for school improvement has led to a related increase in research-practice partnerships (RPPs) that address problems of practice. Yet, little research has centered on how the myriad challenges to such partnerships can be overcome, such as bridging the cultural divide between universities and their school-based partners. Thus, the purpose of this paper is to examine how social capital was developed among the members of a steering committee in a RPP between a university and a 12-district consortium of predominantly rural, high-poverty school districts to develop and implement a professional development initiative for rural school leaders. Design/methodology/approach: Data for this phenomenological single case study were collected over a one-year period through participant observations, document analysis and semi-structured interviews with ten steering committee members. Data were inductively and deductively coded through multiple rounds of analysis, which drew on the structural and cognitive elements of social capital (Uphoff, 2000). Findings were triangulated and member checked for trustworthiness. Findings: The analysis of the data revealed three key ways in which social capital was developed among members of the steering committee to overcome the cultural challenges of RPPs to develop and implement a professional development initiative for rural school leaders: providing an open but focused structure, ensuring inclusive and respectful discussion and negotiating roles and ideas. Originality/value: The findings provide a fine-grained illustration of how intentional efforts to develop social capital among members in a co-design team can assist in bridging the cultural boundaries often encountered in RPPs.